Community Based Screening for Diabetes and Prediabetes using the Indian Diabetes Risk Score among Adults in a Semi-Urban Area in Kathmandu, Nepal - Silvanus, Vinutha; Dhakal, N; Pokhrel, A; Baral, BK; Panta, PP (Nepal Medical College Journal, 2019)
Diabetes has been recognized as a “global health emergency” with an estimated 9% of adults being affected. However, about half of these adults remain undiagnosed. Conventional screening tools like fasting plasma glucose (FPG), oral glucose tolerance testing (OGTT) and glycosylated haemoglobin (HbA1c) can be inconvenient and expensive in a community-based setting. The Indian Diabetes Risk Score (IDRS) is a simple, non-invasive tool which has been validated for use in the Indian population. Age, abdominal obesity, family history of diabetes and physical activity levels have been weighted for a maximum score of 100. Persons with IDRS of <30 are categorized as low risk, 30-50 as medium risk and those with > 60 as high risk for diabetes. A community based, cross-sectional, analytical study was planned to assess the performance of IDRS among adults in a semi-urban area in Kathmandu, Nepal. A total of 256 (170 female, 86 male) persons without diabetes from 260 households were screened during the study period. A majority (46.09%) were classified as high risk, 44.53% as moderate risk and 9.38% as low risk for developing diabetes. Among them, 162 (63.28%) volunteered for definitive testing. The prevalence of undiagnosed diabetes and prediabetes was 4.32% (95% CI: 1.75% to 8.70%) and 7.14% (95% CI: 3.89% to 12.58%) respectively. IDRS predicted the combined risk of diabetes and prediabetes with sensitivity of 84.21% and specificity of 55.24% in adults with score of 60 and above. The area under the ROC curve (AUC) of IDRS for identifying diabetes and prediabetes was 0.69 as compared to the gold standard (2hour Plasma Glucose) AUC of 0.98. IDRS may be a suitable screening tool for diabetes and prediabetes in the adult Nepalese study population.